Inter-state variations in economic growth: Does size and composition of state spending on education matter? - Ram, K.; Kaur, Simrit (2010)
Various types of government spendings have differential impacts on economic growth, implying that there is a great potential to improve the efficiency of government spending by re-allovating resources among sectors. In this backdrop, the article examines how the size of public spending on education impacts the level and growth of Per Capita Income in 14 states of India for the period 1990-91 to 2007-08. Generalised Estimating Equations (GEE) have been applied to estimate the impacted. Economic growth, an outcome variable, has been measured in terms of Per Capita State Net Domestic Product, while the explanatory variables include Per Capita Public Expenditure on education and economic activities. The empirical findings confirm that investment on education has higher and more significant impact in stimulating growth. State spending on education have higher output elasticities as compared to state spending on other 'social services'. - Reproduced.
Keywords: Educational expenditure; Economic growth